2001
DOI: 10.1520/jfs14950j
|View full text |Cite
|
Sign up to set email alerts
|

A New Perspective in the Estimation of Postmortem Interval (PMI) Based on Vitreous [K+]

Abstract: The relation between the potassium concentration in the vitreous humor, [K+], and the postmortem interval has been studied by several authors. Many formulae are available and they are based on a correlation test and linear regression using the PMI as the independent variable and [K+] as the dependent variable. The estimation of the confidence interval is based on this formulation. However, in forensic work, it is necessary to use [K+] as the independent variable to estimate the PMI. Although all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 11 publications
1
41
0
4
Order By: Relevance
“…However, the authors do state that most studies have found a useful relationship [20]. Over the years, many scientists have confirmed the existence of this relationship and created different formulas to estimate the time of death with varying accuracy [33][34][35]. Many of the statistical models and equations derived to estimate time since death are based on the assumption that the postmortem increase in vitreous potassium is fairly linear with time and changes at a constant rate [23].…”
Section: Applications Electrolytesmentioning
confidence: 99%
“…However, the authors do state that most studies have found a useful relationship [20]. Over the years, many scientists have confirmed the existence of this relationship and created different formulas to estimate the time of death with varying accuracy [33][34][35]. Many of the statistical models and equations derived to estimate time since death are based on the assumption that the postmortem increase in vitreous potassium is fairly linear with time and changes at a constant rate [23].…”
Section: Applications Electrolytesmentioning
confidence: 99%
“…which may presumably cause specific time-dependent changes in metabolism and sub-cellular structures that may be used to determine PMI. Indeed, many sophisticated methods have been used to find reliable markers for the estimation of PMI, including the analysis of potassium concentration in vitreous humor [8][9][10][11] and postmortem protein degradation within different tissues [12,13]. In addition, some researches have been focused on the degradation of nucleic acid including DNA and RNA [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…At present time, forensic medicine needs essential renewal of the techniques of DCP estimation. It is related with the fact that existing methods depend on multiple factors of external environment and circumstances of death [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Existing lack of modern, objective techniques of DCP estimation stimulates the search and development of novel techniques for investigation of postmortem changes in human biological tissues and fluids [23].…”
Section: Introductionmentioning
confidence: 99%